MODEL RAD DALAM PERANCANGAN FRONT END APLIKASI PAYMENT POINT ONLINE BANK (PPOB) BERBASIS ANDROID - Dian Ambar Wasesha; Frieyadie Frieyadie (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
The conventional purchase of credit by sending sms to the agent server is often has problem. The error was caused by different format of SMS for each server. This error has an impact on the high cost of using SMS. Another problem when the customer wants to check the electricity bill, the website provided by PLN is less attractive or have to come directly to the PLN payment counter. With these problems, an Android-based application was developed to provide convenience in purchasing credit without worrying about writing format errors and checking until payment of various types of bills becomes more efficient. Bill payments become more practical in one unit, so there is no need to go to different payment counters each month and not get stuck in a long queue that wash time. Development model of this PPOB application is RAD which consists of business modeling, data modeling, process modeling, application development and testing.